THE BASE COMPOSITION OF RIBONUCLEIC ACID IN LAMPBRUSH CHROMOSOMES, NUCLEOLI, NUCLEAR SAP, AND CYTOPLASM OF TRITURUS OOCYTES - Edström, J. -E. (The Rockefeller University Press, 1963)
The base composition of RNA's extracted from chromosomes, nucleoli, nuclear sap, and cytoplasm of Triturus oocytes has been determined by microelectrophoresis. The chromosomal RNA has a content of guanine+cytosine equal to that of DNA, but there is no complementarity in the composition as for DNA. Nuclear sap contains a highly variable RNA with a tendency towards high uracil values. Nucleolar and cytoplasmic RNA's are similar in composition and both are of the guanine-cytosine rich type. The chromosomes and nucleoli contain roughly equivalent amounts of RNA, somewhat less than is present in the nuclear sap. The RNA/DNA ratio of the whole chromosomes is about 10. However, the ratio in the synthetically active regions, the loops, is much higher, since the loops contain all the chromosomal RNA but only a small fraction of the DNA.